The Jounal of the Computer Society of India (Priyalata Pal,Computer Society of India National, 2000)
Issue No: 4( Vol 30,2000) 1-4(Vol 31,2001) 2,4(Vol 32,2002) 1-3(Vol 33,2003) Bound together
Keywords: MBA